2003
DOI: 10.1242/jeb.00352
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of chronic hypercapnia by the European eelAnguilla anguilla

Abstract: SUMMARYEuropean eels were exposed for 6 weeks to water CO2 partial pressures (PCO2) from ambient (approx. 0.8 mmHg), through 15±1 mmHg and 30±1 mmHg to 45±1 mmHg in water with a total hardness of 240 mg l–1 as CaCO3, pH 8.2, at 23±1°C. Arterial plasma PCO2 equilibrated at approximately 2 mmHg above water PCO2 in all groups, and plasma bicarbonate accumulated up to 72 mmol l–1 in the group at a water PCO2 of 45 mmHg. This was associated with an equimolar loss of plasma Cl–, which declined to 71 mmol l–1 at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 38 publications
2
53
1
Order By: Relevance
“…The data from the present study comprise the first report of U crit performance in a fish with bimodal respiration, but A. calva, L. oculatus and M. cyprinoides are all capable of sustained exercise at speeds greater than 2BLs -1 (Farmer and Jackson, 1998;Seymour et al, 2007), which was the U crit measured for G. carapo. The normoxic U crit of G. carapo is similar to that of unimodal water-breathing species with 'anguilliform' locomotion, such as Anguilla anguilla (McKenzie et al, 2003), but G. carapo is significantly less athletic than 'subcarangiform' swimmers of similar size at similar temperatures, such as Leuciscus cephalus, Cyprinus carpio or Dicentrarchus labrax (Claireaux et al, 2006;McKenzie et al, 2007b). The relatively limited aerobic swimming performance of the knifefish is consistent with the species' ecology: it inhabits slow-moving turbid waters, where it uses its electrical sense to hunt for prey (Graham, 1997) and it is reported to bury in the mud if it is exposed to sudden rapid currents (Graham, 1997).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The data from the present study comprise the first report of U crit performance in a fish with bimodal respiration, but A. calva, L. oculatus and M. cyprinoides are all capable of sustained exercise at speeds greater than 2BLs -1 (Farmer and Jackson, 1998;Seymour et al, 2007), which was the U crit measured for G. carapo. The normoxic U crit of G. carapo is similar to that of unimodal water-breathing species with 'anguilliform' locomotion, such as Anguilla anguilla (McKenzie et al, 2003), but G. carapo is significantly less athletic than 'subcarangiform' swimmers of similar size at similar temperatures, such as Leuciscus cephalus, Cyprinus carpio or Dicentrarchus labrax (Claireaux et al, 2006;McKenzie et al, 2007b). The relatively limited aerobic swimming performance of the knifefish is consistent with the species' ecology: it inhabits slow-moving turbid waters, where it uses its electrical sense to hunt for prey (Graham, 1997) and it is reported to bury in the mud if it is exposed to sudden rapid currents (Graham, 1997).…”
Section: Discussionmentioning
confidence: 80%
“…The relative partitioning of M tO2 between water and air at IMR was also similar to a previous report, which found that approximately 35% of M tO2 was derived from air in normoxia (Liem et al, 1984), very similar to the present study, rising to approximately 75% in hypoxia at ~10kPa (Liem et al, 1984), compared with 85% at ~4kPa in the present study. The AMR and net AS of the knifefish were similar to that of the anguilliform swimmer A. anguilla but less than that of subcarangiform swimmers (L. cephalus, C. carpio and D. labrax) of similar size at similar temperatures (McKenzie et al, 2003;McKenzie et al, 2007b;Claireaux et al, 2006).…”
Section: J Mckenzie and Othersmentioning
confidence: 71%
“…The ability to regulate pH e during hypercapnia in P. hypophthalmus is also highly developed compared with several water-breathing fishes, such as the common carp Cyprinus carpio, which recovered 50% of the initial pH e disturbance after 48 h exposure to 8 mmHg CO 2 (Claiborne and Heisler, 1984) and the white sturgeon Acipenser transmontanus, which only compensated 35% of pH e after exposure to 28 mmHg for 72 h (Crocker and Cech, 1998). The European eel exhibits a medium capacity for acid-base regulation, compensating 75% of its disturbance after 6 weeks at a P CO2 of 15 mmHg (McKenzie et al, 2003). P. hypophthalmus thus shows an acid-base regulatory capacity during a respiratory acidosis in line with active water-breathers such as cod and rainbow trout, which compensate the full pH e disturbance within 24 h of exposure to 7.5 and 15 mmHg, respectively (Eddy et al, 1977;.…”
Section: Results and Discussion Acid-base Regulation During Hypercapniamentioning
confidence: 99%
“…, while arterial blood oxygen saturation is halved (McKenzie, 2003). How eels regulate heart rate during hypoxic hypercapnia is unknown.…”
Section: Discussionmentioning
confidence: 99%